The Significance of the Information Technologies in the Functioning of the Network Organisations - Mesjasz-Lech, A. (Электронное моделирование, 2007)
The paper presents the possibility of use of IT in network organisations and its influence on efficiency of network organisations functioning, especially in realisation its the uppermost goals.